Quality of Solid Organic Fertilizer from Moringa Leaves and Peanut Shells with Banana Peel Bioactivator - Mustikasari, Nur Afifah; Asngad, Aminah (Universitas Muhammadiyah Surakarta, 2023)
Fertilizer is a material added to the soil to meet the needs of plant growth and production. Moringa leaves and peanut shells can be used as solid organic fertilizer with the addition of banana peel bioactivator. The purpose of this study was to determine the quality of solid organic fertilizer from moringa leaves and peanut shells with banana peel bioactivator through observation of sensory properties and testing nutrient content. This study used an experimental research method with a complete randomized design (CRD) with a factorial pattern. The first factor was the ratio of ingredients (K1 = 300 g of moringa leaves and 200 g of peanut shell soil; K2 = 200 g of moringa leaves and 300 g of peanut shells). The second factor was dose of banana peel bioactivator (B1 = 25 ml, B2 = 30 ml). The K1B2 treatment had the characteristics of mature organic fertilizer. K1B1 and K1B2 treatments have the highest pH, which is 7. The K1B1 treatment has the best nutrient content with 3.42% nitrogen, 0.11% phosphorus, and 0.22% potassium. The study can be concluded to be that quality organic fertilizer is in accordance with SNI 19-7030-2004.